2020
DOI: 10.1002/14651858.cd005583.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylorieradication for the prevention of gastric neoplasia

Abstract: Helicobacter pylori eradication for the prevention of gastric neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 91 publications
0
101
0
6
Order By: Relevance
“…For NCGA, which accounts for most gastric cancer cases globally, H pylori infection plays a leading role in pathogenesis, with an attributable risk of 80%-90%. 53,54 Although an estimated 4.4 billion people worldwide are infected with H pylori, there are marked global and regional variations in prevalence. In high-prevalence areas, colonization generally occurs in early childhood, 7 which is 39 Rate ratio Japan 1.7 (0.77-3.9) 5.6-6.5 a China 0.37 (0.16-0.86) 1.8-7.9 a important because it is the cumulative time of exposure to H pylori infection that is a strong determinant of cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…For NCGA, which accounts for most gastric cancer cases globally, H pylori infection plays a leading role in pathogenesis, with an attributable risk of 80%-90%. 53,54 Although an estimated 4.4 billion people worldwide are infected with H pylori, there are marked global and regional variations in prevalence. In high-prevalence areas, colonization generally occurs in early childhood, 7 which is 39 Rate ratio Japan 1.7 (0.77-3.9) 5.6-6.5 a China 0.37 (0.16-0.86) 1.8-7.9 a important because it is the cumulative time of exposure to H pylori infection that is a strong determinant of cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori eradication can reduce the risk of gastric cancer, as well as effectively prevent peptic ulcer and H. pylori ‐associated dyspepsia. The data indicate that the implementation of the “ H. pylori eradication strategy” for preventing gastric cancer will be cost‐effective in Asian countries with a high incidence of gastric cancer . In China, endoscopy and the H. pylori test and most drugs for eradicating H. pylori have a low cost, and the detection rate of early gastric cancer is low .…”
Section: H Pylori Infection and Gastric Cancermentioning
confidence: 99%
“…The latter is relevant because initial H. pylori treatment is only 50%‐85% successful, persistent H. pylori infection may be associated with serious long‐term sequelae, symptoms are not a reliable sign of the presence or absence of infection after treatment, and patients may desire evidence that the infection has cleared . Furthermore, meta‐analyses have shown that eradication of H. pylori promotes ulcer healing, prevents ulcer recurrence, and decreases the incidence of gastric malignancy …”
Section: Background and Aimsmentioning
confidence: 99%